Faktor-Faktor yang Berhubungan dengan Kunjungan Postnatal Care (PNC) (Studi Kasus di Puskesmas Wanasari Kabupaten Brebes) - Zulfani, Nazla Fairuz; Azinar, Muhammad (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Brebes Regency had the highest number of maternal mortality in Central Jawa, which were 62 in 2020, 105 in 2021, and 50 in 2022, dominated by postpartum mortality. One of the areas that contributed to maternal mortality is Puskesmas Wanasari. It could be prevented by conducting Postnatal Care (PNC) visits, but the percentage of the third PNC visit (KF3) in Puskesmas Wanasari had not reached the setting targets in 2020 and 2021; and each PNC visits (KF1, KF2, KF3) were likely to decreased. The purpose of this study is to analyze the factors related to PNC visits at Puskesmas Wanasari. The type of study is analytical observational quantitative with cross sectional design. The sample set was 94 postpartum women who were taken using proportionate random sampling technique. Data were analyzed using chi square test or its alternative. The result shows that the delivery methods (p value 0.001), role of midwives (p value 0.022), family supports (p value 0.035), and pospartum danger signs (p value 0.015) are significantly related to PNC visits in Puskesmas Wanasari, while the other variables, such as age, education levels, employment status, and accessibility are not related to. Therefore, postpartum mothers are recommended to fulfill PNC visits at least 3 times even though they gave birth normally and have no health problems. Moreover, health workers are recommended to increase home visits, especially for them who dropped out of PNC visits. Also intensify education for them who likely believe will not be at risk during postpartum period.